Vertical Green: An Urban Farm for Village Living in the City - Gao, Bolong (Auckland University of Technology, 2023)
This thesis research, Vertical Green, explores the possibilities of growing food in the urban context, navigating issues including food safety and food security for city dwellers. The design proposal responds to the urban development in Jiading, a suburb in Shanghai, China. The proposal tests the opportunities of adapting an existing twenty-one-story residential building through the addition of an increased threshold between interior and exterior, making space for vertical vegetable growing. This design brings together various programmes of farming including tool storage, food storage, and food processing, as well as community gathering and communal dining. Developing an urban farm located on the threshold in this way brings increased interaction between living space and farming space so that the design provides an opportunity for resident well-being and social engagement alongside healthy food production. This architectural proposition was landed in the thesis through the research of the question, “What are the opportunities for village living and food security in contemporary Shanghai through high-rise building adaptation?” The project is intentionally seeking out the community’s unique ‘ways of living’ within the residential compound. The contextual research evaluates several values and facts that urban residents live in their village behaviour, especially in food sourcing. The research borrows methods from ecological mapping to observe food seeking behaviours in the neighbourhood and to understand the spatial and behavioural conditions of the proposed system. The green bean is used as a test food plant to identify relationships across humans, plants and climate in ecological cycles. The research discovers that there are positive aspects of re-thinking food production in an urban setting by paying attention to food safety and food security in village living. The high-rise building adaptation is capable to support aspects of village living, by having a vertical farm located on the threshold in the designed way. The ecological mapping identifies unusual food-sourcing methods in an urban compound and releases the intertwined connections between one testing plant and the ecological system. Overall, the thesis describes the embracement of co-living between urban living and farming explored through the architectural approach, providing a healthier opportunity for urban residential intervention.